Analysis of self-behavior and juvenile delinquency - Asmuni, Hetty Susilawati (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2007)
In this present research, the relationship between self-behavior and delinquency was investigated. The research was conducted by using 3 parts of questionnaire as the instrument of measurement. Part B of the questionnaire was taken from the Jesness Behavioral Checklist (JBC) which is designed to provide a systematic way of recording data about social behavior. The JBC are comprise of 80 items or subscales which measure 14 bipolar behavioral factors. The I 4 subscales of self-behavior that were being measured included: Unobtrusiveness, Friendliness, Responsibility, Considerateness, Independence, Rapport, Enthusiasm, Sociability, Conformity, Calmness, Communication, Insight, Social Control, and Anger Control. Participants were 230 delinquent juveniles from Henry Gurney School. located in Telok Mas, Melaka, and 190 juveniles from nondelinquent institutions as a control sample. Participants for the control sample were randomly selected at the area around Kota Bharu, Kelantan. Spearman Rho Correlation Test and Mann-Whitney Test were used to analyze the data Results indicated that: (I) there is a significant correlation between subscale of unobtrusiveness, friendliness, conformity and social control toward self-reported delinquency for both delinquent . and nondelinquent institution groups. Significant correlation between subscale of rapport, responsibility and calmness toward delinquency were present only among the nondelinquent institution group. Other subscales of self-behavior showed no correlation with delinquency for both delinquent and nondelinquent institution groups; (2) there is no significant difference in the mean score between delinquent and nondelinquent institution groups with regard to each subscale of self-behavior, and (3) no significant difference in the mean score between delinquent and nondelinquent institution groups with regard to delinquent activities.